An Ameliorated GWO-SQP Model for Enabling an Effective Radar Communication in MIMO Systems - Reddy, S. V. Bharath Kumar; Kumar, Ch. Sumanth (International Journal of Intelligent Systems and Applications in Engineering, 2024)
One of the most demanding and important tasks in Multiple Input Multiple Output (MIMO) radar systems is the design and development of Orthogonal Frequency Division Multiplexing (OFDM) – Linear Frequency Modulation (LFM) waveforms. Also, increasing the pulse characteristics of spatially synthesized signals is crucial in MIMO systems since it makes it possible to successfully eliminate grating sidelobes. Various joint optimization strategies have been developed in the existing studies to enhance the overall performance of radar communication systems. It still has limitations due to issues with difficult to comprehend calculations, a high error rate, and reduced performance. To enhance the pulse compression qualities and suppress grating sidelobes, the proposed research work aims to implement a Gray Wolf Optimization (GWO) – Sequential Quadratic Programming (SQP) mechanism. In this particular instance, the modification is carried out to optimize the frequency steps of the anticipated LFM waveform with balanced orthogonal and sidelobe features. By using different pulse compression properties, the performance and results of the proposed GWO-SQP based joint optimization model are evaluated and compared through simulation analysis. The results show that, in comparison to the previous methodologies, the proposed optimization model offers better performance outcomes. For comparative assessment, the parameters such as maximum ASP, mean ASP, and mean CP are validated and compared for the existing and proposed models with respect to different Bs(MHz) including 2.72, 2.44, 2.16, 1.81 and 1.46. The results indicate that the proposed GWO-SQP could effectively reduce ASP with the average values of 0.12 (Max ASP), 0.10 (Mean ASP) and 0.32(Mean CP) values respectively.